2018
DOI: 10.1002/jmv.25358
|View full text |Cite
|
Sign up to set email alerts
|

Umifenovir susceptibility monitoring and characterization of influenza viruses isolated during ARBITR clinical study

Abstract: Antiviral drugs can play a significant role in the control of influenza. Umifenovir (Arbidol) is licensed and widely used in Russia for the prophylaxis and/or treatment of influenza. We evaluated the susceptibility to umifenovir of reference influenza A and B viruses and influenza A viruses isolated from patients in the ARBITR clinical trial in 2012‐2014 seasons. Using an MDCK cell‐based enzyme‐linked immunosorbent assay (ELISA), we showed that the replication of antigenically dominant human influenza A and B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Mice with respiratory chain defects were highly susceptible to viral infection and exhibited significant lung inflammation [2]. Oxidative and nitrosative stress may also contribute to reduced All 18 clinical isolates of influenza A viruses that were obtained before and during therapy were susceptible to Umifenovir with 50% effective concentration ranging from 8.4 +/− 1.1 to 17.4 +/− 5.4 µM without the development of drug-resistant variants [22]. Experimental studies at concentrations of 25-100 mg/mL proved the direct antiviral activity of Umifenovir on the early viral replication of severe acute respiratory syndrome (SARS) virus in the cultured GMK-AH-1 cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mice with respiratory chain defects were highly susceptible to viral infection and exhibited significant lung inflammation [2]. Oxidative and nitrosative stress may also contribute to reduced All 18 clinical isolates of influenza A viruses that were obtained before and during therapy were susceptible to Umifenovir with 50% effective concentration ranging from 8.4 +/− 1.1 to 17.4 +/− 5.4 µM without the development of drug-resistant variants [22]. Experimental studies at concentrations of 25-100 mg/mL proved the direct antiviral activity of Umifenovir on the early viral replication of severe acute respiratory syndrome (SARS) virus in the cultured GMK-AH-1 cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 has been pandemic, a variety of antiviral drugs have been investigated on patients with COVID-19 (12). Arbidol is a Russian antiviral drug that seems to be effective against many viruses including in uenza A, B, and C, respiratory syncytial virus (RSV), severe acute respiratory syndromerelated coronavirus (SARS-CoV), adenovirus, parain uenza, poliovirus, rhinovirus, coxsackievirus, zika virus, hepatitis B and C viruses (13)(14)(15). It has been demonstrated that Arbidol has a dual effect on cell attachment and replication, and thus a broad-spectrum effect on viruses (16,8), so it is administered for post-exposure prophylaxis and treatment (17).…”
Section: Discussionmentioning
confidence: 99%
“…In einer prospektiven Pilotstudie mit 63 Patienten mit schwerer COVID-19 war die Gabe von Tocilizumab mit einer gesteigerten Überlebenswahrscheinlichkeit assoziiert (Hazard Ratio 2,2, 95 %-KI 1,3–6,7, p < 0,05). IL-6-Spiegel erwiesen sich in dieser Studie jedoch nicht als Prädiktorwert für die Mortalität, wohl aber die D‑Dimere bei Studienbeginn [ 30 ]. Zum jetzigen Zeitpunkt ist noch keine Evidenz für die Wirksamkeit von Tocilizumab bei COVID-19-Patienten vorgelegt worden [ 31 , 32 ].…”
Section: Monokloanale Antikörper Zur Symptomatischen Behandlung Von Iunclassified